A 2-year follow-up study of people with severe mental illness involved in psychosocial rehabilitation. (August 2014) - Svedberg, Petra; Svensson, Bengt; Hansson, Lars; Jormfeldt, Henrika
Abstract Backgrounds. A focus on psychiatric rehabilitation in order to support recovery among persons with severe mental illness (SMI) has been given great attention in research and mental health policy, but less impact on clinical practice. Despite the potential impact of psychiatric rehabilitation on health and wellbeing, there is a lack of research regarding the model called the Psychiatric Rehabilitation Approach from Boston University (BPR). Aim: The aim was to investigate the outcome of the BPR intervention regarding changes in life situation, use of healthcare services, quality of life, health, psychosocial functioning and empowerment. Methods: The study has a prospective longitudinal design and the setting was seven mental health services who worked with the BPR in the county of Halland in Sweden. In total, 71 clients completed the assessment at baseline and of these 49 completed the 2-year follow-up assessments. Results: The most significant finding was an improved psychosocial functioning at the follow-up assessment. Furthermore, 65% of the clients reported that they had mainly or almost completely achieved their self-formulated rehabilitation goals at the 2-year follow-up. There were significant differences with regard to health, empowerment, quality of life and psychosocial functioning for those who reported that they had mainly/completely had achieved their self-formulated rehabilitation goals compared to those who reported that they only had to a small extent or not at all reached their goals. Conclusions: Our results indicate that the BPR approach has impact on clients' health, empowerment, quality of life and in particular concerning psychosocial functioning.